2018
DOI: 10.1002/pcr2.10005
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization, recrystallization, and melting of polymer crystals on heating and cooling examined with fast scanning calorimetry

Abstract: Fast scanning calorimetry (FSC) has been used to investigate the kinetics of nonisothermal crystallization, isothermal crystallization, and melting for semicrystalline polymers (ie, poly(butylene terephthalate, polyphenylene sulfide, and isotactic polypropylene). The scanning rate dependence of enthalpy of melt‐crystallization, cold‐crystallization, and recrystallization obtained from FSC are quantitatively explained on the basis of Ozawa's method. For isothermal kinetics, FSC allows to obtain the annealing‐te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 62 publications
6
49
0
Order By: Relevance
“…The enthalpy of cold crystallization decreases with the heating rate. It is reported that the heating rate dependence on enthalpy of cold crystallization can also be described by the same form of Equation . The present results show that the cold crystallization kinetics of PP can also be explained by Equation .…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The enthalpy of cold crystallization decreases with the heating rate. It is reported that the heating rate dependence on enthalpy of cold crystallization can also be described by the same form of Equation . The present results show that the cold crystallization kinetics of PP can also be explained by Equation .…”
Section: Resultssupporting
confidence: 76%
“…On the basis of Ozawa's model, the cooling rate ( β ) dependence on the heat of fusion (Δ H total ) of many semicrystalline polymers can be described as follows: ΔHtotal=CBexp[]βnormalcβnA{}logββ2nd×12()1ββ2ndββ2nd, where C , B , A , n , β c , and β 2nd are constants, n with a value from 1 to 4, β c is the characteristic cooling rate of domain growth during primary crystallization, and β 2nd is the characteristic cooling rate of secondary crystallization. Secondary crystallization proceeds only at slow cooling rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, understanding the molecular behavior and influencing factors in the force‐induced melting is of fundamental importance to design high‐performance polymer materials . The introduction of novel techniques, such as in situ atomic force microscopy (AFM), modulated and high speed calorimetry, microbeam X‐ray scattering, solid‐state nuclear magnetic resonance (NMR), and the combination of related techniques have especially expanded the knowledge of chain behaviors in force‐induced melting . Nevertheless, the corresponding mechanism is still not completely understood due to the relatively complex deformation behaviors in bulk materials .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research activities in the field of polymer crystallization have been focused on three systems: bulk, solution, or thin films. In bulk, recent progress includes new perspectives on crystallization behavior and newly discovered crystal structures/phases . Flow‐induced crystallization has also attracted intense attention and most of the studied systems are bulk although polymer solution has also been investigated .…”
Section: Introductionmentioning
confidence: 99%